Increased captures of the critically endangered leatherback turtle (Dermochelys coriacea) around New Zealand: the contribution of warming seas and fisher behavior - Dunn, Matthew R.; Finucci, Brittany; Pinkerton, Matthew H.; Sutton, Philip; Duffy, Clinton A.J. (Frontiers in Marine Science, 2023)
Five species of sea turtles are known to occur in New Zealand waters, with the leatherback turtle (Dermochelys coriacea) being the most frequently reported. Although all sea turtles are protected in New Zealand waters, New Zealand currently has no fisheries bycatch mitigation measures for turtles. Between fishing years 2007–08 and 2020–21 (annual starting 1 October), fishers and fishery observers reported 217 captures of leatherback turtles in New Zealand waters, an average of 15.5 caught annually. Nearly all leatherback captures (97.7%) were reported from surface longline fisheries. Fisheries observers have provided little coverage of the main fishery capturing leatherbacks, and most captures (85.3%) were reported by fishers. Within the main fishery, just 9.4% of the vessels reported 94.5% of the leatherback captures, and one vessel reported 40.4% of all captures. Non-reporting of captures seems plausible. Reported leatherback captures increased substantially to 50 in 2020–21. A generalized additive model (GAM) estimated an increasing probability of capture that broadly matched the year trend in reported captures. The GAM estimated higher probability of capture with increasing SST from a constant-over-time spatial pattern of monthly sea surface temperature (SST). Therefore much of the increase in bycatch could be explained by the fleet moving into warmer areas where the probability of leatherback capture was higher. About two-thirds of the SST warming experienced by the fishery (1.5°C of 2.4°C) between 2007–08 and 2021–22 was attributable to changes in the location and/or timing of fishing, with about one third occurring because of warming of the whole area over time. Capture mitigation measures could therefore include restricting fishing in turtle ‘hotspot’ times and areas. New Zealand waters should be recognized as an important seasonal foraging ground for leatherback turtles where capture mitigation measures are necessary.